2011
DOI: 10.1186/1471-2156-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Arachnomelia syndrome in Simmental cattle is caused by a homozygous 2-bp deletion in the molybdenum cofactor synthesis step 1 gene (MOCS1)

Abstract: BackgroundArachnomelia syndrome is an autosomal recessive inherited disease in cattle. Affected calves die around birth and show malformations of the skeleton mainly affecting the legs, the spinal column and the skull. A number of arachnomelia syndrome affected Simmental calves were recently detected by a surveillance system of anomalies with a peak of more than 120 recorded cases in the year 2006. The causative mutation was previously mapped to a 9 cM-region on bovine chromosome 23. We herein report the fine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The UMD3.1 reference coordinates could be determined for 59 of the OMIA entries (Additional files 6 and 7). The 2bp deletion in MOCS1 responsible for Arachnomelia (OMIA 001541–9913; [20]) could be detected in a known heterozygous carrier of the defective variant. An amino acid exchange in RASGRP2 has been proposed to be the causal variant for a bleeding disorder in a Simmental animal (Thrombopathia, OMIA 001003–9913; [21]).…”
Section: Resultsmentioning
confidence: 99%
“…The UMD3.1 reference coordinates could be determined for 59 of the OMIA entries (Additional files 6 and 7). The 2bp deletion in MOCS1 responsible for Arachnomelia (OMIA 001541–9913; [20]) could be detected in a known heterozygous carrier of the defective variant. An amino acid exchange in RASGRP2 has been proposed to be the causal variant for a bleeding disorder in a Simmental animal (Thrombopathia, OMIA 001003–9913; [21]).…”
Section: Resultsmentioning
confidence: 99%
“…This polymorphism is known to modulate the clinical phenotype in LQTS patients (QTc, arrhythmogenic events) 7 in a sex-specific manner, with additional QT prolongation in male but not in female patients, suggesting that this polymorphism might be susceptible to differential sex hormonal influence and could thus contribute to progesterone’s particularly pronounced QT interval–shortening effects observed in this patient.…”
Section: Discussionmentioning
confidence: 89%
“…However, a polymorphism in KCNE1 (Asp 85 Asn), the beta-subunit to KCNQ1 /KvLQT1, was detected. This polymorphism may play a role in drug-induced LQTS and has been observed more frequently in LQTS patients, where it contributes to the clinical phenotype (QT duration, arrhythmogenic events) 7 . Her father and mother have normal QTc durations, and there have been no confirmed cases of sudden death in the family, although her maternal uncle died in his 20s, reportedly of a seizure, and a maternal cousin drowned at 16 years of age with no apparent cause.…”
Section: Case Reportmentioning
confidence: 99%
“…For example, common aminoacid altering single nucleotide polymorphisms (SNPs) in KCNE1 (D85N) [64], KCNH2 (K897T) [65], and SCN5A (H558R) [66, 67] exert modest electrophysiologic effects that can modulate the in vivo or in vitro phenotypic expression of certain LQT1-, LQT2-, and LQT3-causative mutations, respectively. Furthermore, recent studies have also identified a role for non-coding SNPs within critical genomic regions, such as the promoter or 3′ untranslated regions, known to regulate the expression of established LQTS-susceptibility genes (Table 2).…”
Section: Genetic and Electrophsyiologic Basis Of Long Qt Syndromementioning
confidence: 99%